2021
DOI: 10.3390/nano11081939
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of the α-Tocopherol-Derived Metabolite α-13′-Carboxychromanol from Bacterial Nanocellulose Wound Cover Improves Wound Healing

Abstract: Inflammation is a hallmark of tissue remodeling during wound healing. The inflammatory response to wounds is tightly controlled and well-coordinated; dysregulation compromises wound healing and causes persistent inflammation. Topical application of natural anti-inflammatory products may improve wound healing, in particular under chronic pathological conditions. The long-chain metabolites of vitamin E (LCM) are bioactive molecules that mediate cellular effects via oxidative stress signaling as well as anti-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Many natural products with therapeutic potential have been applied in clinical practice and have attracted increasing interest in recent years 23 . Meanwhile, an increasing number of natural products combined with other dressings and agents for the treatment of chronic wounds have achieved satisfactory results 24 , 25 . Naringenin (the chemical structure is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Many natural products with therapeutic potential have been applied in clinical practice and have attracted increasing interest in recent years 23 . Meanwhile, an increasing number of natural products combined with other dressings and agents for the treatment of chronic wounds have achieved satisfactory results 24 , 25 . Naringenin (the chemical structure is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the NBCH have great potential as an ideal wound dressing for efficient and rapid healing in patients with diabetes. For another example, Adrian T. Press et al [ 106 ] used bacterial nanocelluloses (BNC) as wound dressing to load α -13′-COOH (α-Tocopherol-Derived Metabolite), which was directly applied to wounds using a splinted wound mouse model under the condition of diabetes, to investigate their effects on wounds’ proinflammatory microenvironment and wound healing. The results showed that BNC could control the release of α -13′-COOH and promote wound healing and wound closure.…”
Section: Types Of Nanocarriers Used For the Treatment Of Diabetesmentioning
confidence: 99%
“…The main pathological abnormalities in diabetic wounds are vascular problems and long-term inflammatory response, so single-therapy approaches often fail to achieve the desired results. Studies have shown that wound closure is a closely regulated and highly coordinated process between pro- and anti-inflammation [ 45 ]. Therefore, intervention in the healing process to reduce the inflammatory response and stimulate tissue regeneration is currently essential to achieve the faster healing of diabetic wounds [ 46 ].…”
Section: Diabetic Wounds and Diabetic Dressingsmentioning
confidence: 99%